IBS: Pathophysiology and Management Challenges - Akram, Muhammad; Umaru, Isaac John; Mahmood, Abid; Hasan, Mohammed Khudhair; Abdulghafoor, Hind A.; Khan, Fahad Said; Ozdemir, Fethi Ahmet; Sołowski, Gaweł; Ali, Jaouher Ben; Jehan Mohammed Al-Musawi, Jehan Mohammed (Darul Yasin Al Sys, 2025)
Irritable Bowel Syndrome (IBS) is a widespread functional gastrointestinal ailment with chronic abdominal pain, change in bowel movements, and reduced quality of life as hallmarks. Unlike organic diseases, IBS is idiopathic—diagnosed in the absence of structural or biochemical disturbances, which makes disease management more difficult. The causes of IBS are heterogeneous: dysregulation of gut-brain axis, visceral hypersensitivity, motility disorders, changes in microbiome, and psychosocial aspects contribute to it. This article explains causes of IBS, symptomatology, diagnostic criteria, and treatment options multidisciplinary with a focus on tailored dietary intervention, medication, psychotherapy, as well as alternative methods.